Validity of the running repeated sprint ability test among playing positions and level of competitiveness in trained soccer players - Aziz, A. R.; Mukherjee, S.; Chia, M. Y. H.; Teh, K. C. (International Journal of Sports Medicine, 2008)
The purpose of this study was to examine the construct validity of the running repeated sprint ability (rRSA) test to discriminate performances between: i) various playing positions (Study 1), and ii) teams of different level of competitiveness (Study 2), in trained soccer players. Study 1 comprised clubs' players participating in the top local professional league. Study 2 comprised professional and semiprofessional players from the National Under-23 and Youth squads respectively, and amateur-level players from a University team. The rRSA test protocol consisted of either 6 or 8 repetitions of 20-m all-out sprints, interspersed with a 20-s active recovery period. There were significant differences in the rRSA performance between goalkeepers and outfield-positions (p < 0.01). Forwards had significantly better rRSA performance compared to defenders and midfielders (F ratio = 4.147, p = 0.02). Performance in the rRSA was superior in teams with relatively higher competitiveness (F ratio = 3.973, p = 0.02). The rRSA is a specific physical or fitness attribute of an outfield-position player, and may be of greater importance to the forwards' position. Performance in the rRSA also seems to be associated with a higher level of competitiveness and/or adaptation to resistance training. These data support the construct validity of the rRSA test in trained soccer players.